The barratt impulsiveness scale - 11 among a portuguese sample of female juvenile delinquents and community youths - Pechorro, Pedro (2019)
Impulsivity among incarcerated female juvenile offenders is an understudied area of research. The aim of this study was to examine the psychometric properties of the Barratt Impulsiveness Scale version 11 (BIS-11) among a Portuguese sample of female participants (N = 377, mean age = 16.23 years, SD = 1.38) recruited from forensic and school contexts. Confirmatory factor analysis revealed the expected six-factor first-order structure, but not the three-factor second-order structure. Acceptable levels of internal consistency were mostly obtained, but some dimensions showed somewhat lower than expected values. Convergent validity with measures of psychopathic and callous-unemotional traits, and discriminant validity with a measure of social anxiety was demonstrated. In terms of criterion-related validity significant associations were found with relevant variables (e.g., age of crime onset, conduct disorder symptoms, alcohol, and drug use). The use of the BIS-11 among female juvenile delinquents and community youth is psychometrically justified and it can be considered a useful measure to identify impulsive adolescents.